Is there an established hemoglobin target range for patients undergoing chronic dialysis?. Issue 4 (6th March 2018) - Shah, Hitesh H.; Fishbane, Steven
Abstract: Anemia is a common complication of advanced chronic kidney disease (CKD). Treatment with erythropoiesis‐stimulating agents (ESAs) remains a common approach in managing anemia of CKD. The 2012 Kidney Disease Improving Global Outcomes Clinical Practice Guideline for Anemia in CKD suggests avoiding ESA therapy use to maintain Hb level above 11.5 g/dL. However, optimal Hb target range in adult patients undergoing chronic dialysis remains unknown. Clinical studies suggest risks associated with normalization of Hb levels in adult patients with CKD. In this article, we briefly review some of these studies and the concerns associated with higher Hb targets in this patient population. We also suggest a target Hb range for adult chronic dialysis patients receiving ESAs. It is currently undetermined if this target Hb range would apply to newer agents that are being studied for anemia management in this population.